Exploring Discourse in Context and in Action - Candlin, Christopher N.; Crichton, Jonathan; Moore, Stephen H. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book combines an authoritative examination of the field of discourse-based research with practical guidance on research design and development. The book is not prescriptive but instead invites expansive, innovative thinking about what discourse is, why it matters to people at particular sites and how it can be investigated. The authors identify a set of questions that, they argue, are crucial for understanding discourse. Part I of the book explores the implications of these questions, providing a comprehensive survey of relevant scholars, theories, concepts and methodologies. Part II addresses these implications, setting out a multi-perspectival approach to resourcing and integrating micro and macro perspectives in the description, interpretation and explanation of data. Part III offers wide-ranging resources to support further reflection and future research. Ultimately, this book offers a new research approach for students, researchers and practitioners in Applied Linguistics to encourage and support research that can be truly impactful through its relevance to social and professional practice.- Resumé vydavatel
Keywords: aplikovaná lingvistika; diskurzivní analýza; sociolingvistika; applied linguistics; discourse analysis; sociolinguistics; elektronické knihy; monografie; electronic books; monographs